2010
DOI: 10.1002/bit.22701
|View full text |Cite
|
Sign up to set email alerts
|

Lipid analysis of Neochloris oleoabundans by liquid state NMR

Abstract: This study is an evaluation of liquid state NMR as a tool for analyzing the lipid composition of algal cultures used for biodiesel production. To demonstrate the viability of this approach, (13)C NMR was used to analyze the lipid composition of intact cells of the algal species, Neochloris oleoabundans (UTEX #1185). Two cultures were used in this study. One culture was "healthy" and grown in conventional media, whereas the other culture was "nitrogen-starved" and grown in media that lacked nitrate. Triglycerid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 72 publications
1
19
0
3
Order By: Relevance
“…This indicated that nitrogen was essential in synthesis of chlorophyll for photosynthesis which also enhanced growth of microalgae. Similar result was also found in Beal et al [18] which showed that nitrogen starved algal paste was yellow green in color and healthy sample was dark green. Figure 2 shows that nitrogen starved cells contained more lipid droplets with increased cell size than the normal cells.…”
Section: Growth Aspects Of N Oculata Under Normal and Nitrogensupporting
confidence: 89%
“…This indicated that nitrogen was essential in synthesis of chlorophyll for photosynthesis which also enhanced growth of microalgae. Similar result was also found in Beal et al [18] which showed that nitrogen starved algal paste was yellow green in color and healthy sample was dark green. Figure 2 shows that nitrogen starved cells contained more lipid droplets with increased cell size than the normal cells.…”
Section: Growth Aspects Of N Oculata Under Normal and Nitrogensupporting
confidence: 89%
“…Singlecomponent standards such as triglyceride oleate (TGO), triglyceride stearate, or triglyceride palmitate have been used to study the fatty acid composition of algal extracts. The matrix effect has not been taken into account when single-component standards have been used for quantitative analyses of lipid content in algal extracts [16,23,31]. If matrix effects are not considered, the results may be misleading owing to overlapping chemical shift regions or resemblance with the matching structures in complex matrices containing a multicomponent system of TG, FFA, and polar lipids as observed in the present studies.…”
Section: Introductionmentioning
confidence: 75%
“…From the detailed NMR spectral interpretation of solvent extracts of algal biomasses and GC-MS analyses, we summarize that algal extracts are composed of the following components: As a general practice reported in the literature, the fat or glyceride content in algal or vegetable oils is determined by use of a single-component external reference such as TGO, triglyceride stearate, or triglyceride palmitate [16,23,31]. This approach might not be appropriate in the case of algal oils for the following reasons:…”
Section: Hsqc-tocsy Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectroscopy has been used to determine the lipid contents of lyophilized biomass [228] and of wet biomass [229]. From the perspective of this review, the most interesting application so far has been the use of liquid state 1 H-NMR for noninvasive quantification of the lipid (triacylglyceride, TAG) content within live cultures [166].…”
Section: Nmr Spectroscopymentioning
confidence: 99%